2020
DOI: 10.2147/ott.s278755
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Motif Protein 38 as a Potential Biomarker and Therapeutic Target in Cancer

Abstract: RNA-binding proteins (RBPs) act as a key factor in gene regulation by governing RNA metabolism. They contribute to the expression and functions of most RNAs by binding to them and forming complexes. RNA-binding motif protein 38 (RBM38), a member of the RBP family, alters the stability and translation of targeted mRNAs to affect various biological processes, such as cell proliferation, cell cycle arrest, and myogenic differentiation. RBM38 contains a highly conserved RNA recognition motif (RRM) consisting of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…11 RBM38, which contains a conserved RNA-binding motif, is involved in modulating the stability and translation of mRNA in cells. 12 To date, a number of studies have reported that RBM38 suppresses tumor growth or progression by regulating the mRNA stability of tumor-associated genes, such as c-Myc, 13 PTEN, 14 p53, 15 MDM2, 16 and p57. 8 Interestingly, there are several regulatory loops modulating tumor progression in cells; for example, c-Myc is found to transcriptionally regulate the expression of RBM38 and form c-Myc-RBM38 complexes in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 RBM38, which contains a conserved RNA-binding motif, is involved in modulating the stability and translation of mRNA in cells. 12 To date, a number of studies have reported that RBM38 suppresses tumor growth or progression by regulating the mRNA stability of tumor-associated genes, such as c-Myc, 13 PTEN, 14 p53, 15 MDM2, 16 and p57. 8 Interestingly, there are several regulatory loops modulating tumor progression in cells; for example, c-Myc is found to transcriptionally regulate the expression of RBM38 and form c-Myc-RBM38 complexes in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Posttranscriptional regulation of mRNA is important for maintaining the homeostasis of cells 11 . RBM38, which contains a conserved RNA-binding motif, is involved in modulating the stability and translation of mRNA in cells 12 . To date, a number of studies have reported that RBM38 suppresses tumor growth or progression by regulating the mRNA stability of tumor-associated genes, such as c-Myc, 13 PTEN, 14 p53, 15 MDM2, 16 and p57 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, its knock-out in mice has shown an elevation of p53 in various cells and tissues such as embryonic fibroblasts, thymus, and spleen, which contributed to their enhanced penetrance to tumors [ 27 ]. RBM38 binds to various genes such as p53, p21, GDF15, mdm2, HuR, and c-myc through their 3ʹUTR AU-rich elements [ 29 ]. RBM38 has also been reported as a critical splice factor of the cardiac, which plays a role in governing heart sarcomerogenesis by regulating the alternative protein isorforms expressions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ectopic expression of RBM38 can inhibit the proliferation of breast cancer cells, while knockdown of RBM38 exhibits an opposite effect in vivo and in vitro ( 52 ). When RBM38 is overexpressed, it inhibits the migration and invasion of breast cancer cells by inducing cell cycle arrest and inhibiting mutant p53-induced epithelial-mesenchymal transition (EMT) ( 5 ). EMT is triggered by individual extracellular signals, including extracellular matrix components, such as collagen and hyaluronic acid, and soluble growth factors, like transforming growth factor–β (TGF-β), fibroblast growth factor (FGF), and epidermal growth factor (EGF).…”
Section: Rna-binding Motif Protein 38 (Rbm38)mentioning
confidence: 99%